Skin Structure, Physiology, and Pathology in Topical and Transdermal Drug Delivery - Brito, Sofia; Baek, Moonki; Bin, Bum Ho (Pharmaceutics, 2024)
Several industries are increasingly focused on enhancing the delivery of active ingredients through the skin to optimize therapeutic outcomes. By facilitating the penetration of active ingredients through the skin barrier, these enhancers can significantly improve the efficacy of various formulations, ranging from skincare products to therapeutic agents targeting systemic circulation. As the understanding of skin physiology and the mechanisms of drug absorption deepen, these industries are adopting permeation enhancers more widely, ultimately leading to better patient outcomes and expanded treatment options. However, the structure and physiological function of the skin can vary according to different factors, such as the area of the body and between individuals. These variations, along with external environmental exposures, aging and pathological conditions, introduce complexities that must be carefully considered when designing effective delivery systems. Considering the intricacies of skin structure and physiology, tailoring systems to account for regional differences, individual variability, and changes induced by environmental factors or disease is critical to optimizing therapeutic outcomes. This review discusses the features of skin structure, physiology, and pathologies, as well as the application of permeation enhancers in these contexts. Furthermore, it addresses the use of animal skin models in transdermal delivery and dermatological studies, along with the latest developments in this field.
Keywords: skin aging; skin disease; skin models; skin physiology; skin structure; transdermal drug delivery